Correlates of work adjustment among employed adults with auditory and visual impairments - Blanca, Antonia Benlayo (2009)
The study was conducted to identify the correlates of work adjustment that enhance the ability through the demographic profile variables of employed adults with auditory and visual impairments in the workplace. The researcher used surveys and interviews to gather data. It was found that as to the correlates of work adjustment of employed adults with hearing impairment, demographic variables such as age, length of service and educational background are deemed present but with slight relationship. As to the employed respondents with visual impairment, the correlates which are length of service, employment status and educational background were significantly related to work adjustment. It was evident in the study that work adjustment is not affected by demographic profile. This shows that the employed adults with auditory and visual impairments are satisfied with their jobs.
Thesis (Ph.D. Special Education)--University of the Philippines, Diliman.
Keywords: People with hearing disabilities -- Employment -- Philippines -- Manila Metropolitan Area; People with visual disabilities -- Employment -- Philippines -- Manila Metropolitan Area; People with disabilities -- Employment -- Philippines -- Manila Metropolitan Area